Die boek Josua gelees teen "n na-eksiliese agtergrond - Lindeque, G. C. (HTS teologiese studies, 2002)
Reading the book of Joshua against a post-exilic backgroundThis article argues that the book of Joshua portrays the idealistic views held by the post-exilic community on the history of Israel. The book displays remarkable similarities with Third Isaiah and with narratives from the post-exilic period. By reading the book of Joshua against a post-exilic background, it obtains theological significance, not as a historical account of the occupation of the land, but as a call for the acceptance of foreigners into the community of the people of YHWH, as well as for the decentralization of religious power. The book owes its final form to a marginalized group, who were in conflict with the religious leaders in Jerusalem. The book of Joshua functioned as a contra-narrative against the exclusive claims made by the returning exiles.